An evidence-based approach for investment in rapid-charging infrastructure. (July 2017) - Serradilla, Javier; Wardle, Josey; Blythe, Phil; Gibbon, Jane
Abstract: To date, real cost data for Electric Vehicle (EV) rapid charging infrastructure is largely missing in the literature, preventing development of economic models to encourage private investment and limiting policy decisions. A business model has been constructed using actual capital expenditure, operating costs and usage data from the Rapid Charge Network project (RCN) which can be used to assist future investment and policy decisions. The model is run under a wide spectrum of EV uptake scenarios to provide plausible answers to a variety of research, policy and investment questions, including minimum growth rates to break even under current policy. Using real-world data we have confirmed that a financial business opportunity does exist for investment in rapid chargers on main highways and have identified the operating area in which a profit can be made. However, since UK EV adoption is still at the Innovators stage in a niche market where innovations in technology, user practices, supporting infrastructure and functionality are still required to achieve wide user acceptance, the case is also made for continued fiscal incentives to encourage investment in rapid-charging infrastructure. Highlights: Uses actual cost and use data to propose credible business model for EV rapid charging. Identifies a profit area for successful operation. Applying 3.3 electricity mark-up over 10 year investment period gives financial return. EV uptake and Drivers' willingness to pay remain key constraints. Fiscal incentives would encourage private investment where demand is uncertain.